PENGARUH KETERSEDIAAN OKSIGEN PADA PRODUKSI EPIGLUKAN OLEH Epicoccum nigrum MENGGUNAKAN MEDIA MOLASES - Miftahul Choiron; Jayus Jayus; Sony Suwasono (Agroindustrial Technology, University of Trunojoyo Madura, 2013)
The compound β-glucan is a polymer of glucose, which is polymerized through betaglycoside bond. The compound β-glucan has anti-tumor benefits, reducing the risk of heartdisease, lowering cholesterol and so forth. The compound β-glucan can be produced by thefungus in ukstraseluler. One of the molds that can produce compounds in the extracellular β-glucan is Epicoccum nigrum, often called epiglucan. The purpose of this study was to determinethe effect of aeration and oxygenation to the production epiglukan by Epicoccum nigrum inmolasses media. This research was conducted using descriptive method with 3 under controlledconditions : anaerobic, aeration and oxygenation in the Stired Continuous Tank Reactor (batchculture). The parameters observed were the biomass (g / L), epiglucan (g/L), reducing sugarcontent (%) and pellet diameter are formed. Biomass and highest epiglikan obtained inoxygenated conditions which amounted to 7.074 g / L and 2.01 g / L. The resulting biomasspellet-shaped with the largest diameter occurs in conditions of oxygenation that is 0.37 mm.residual reducing sugar at the end of fermentation the greatest there is in the anaerobiccondition is 1.529%